PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL PROJECT BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK - Noviana Kusumawati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
The  objectives of  this  research is: (1) generate the PBL learning  model in  the  linear program material to enhance the communication skill of Mathematical valid, (2) obtain the effectiveness of learning mathematics model PBL. Activity of independent variables while the dependent variable mathematics communication  skill. The  results:  (1) equipments  developed valid,  (2)  learning process  using PBL effective,  marked  the achievement  of:  a)  the exhaustiveness indivudually mathematics communication skill test exceed for KKM and classical completeness exceed 70%, b) activity has  a  positive effect on the  mathematics  communication skill, c)  average of  mathematics communication skill test experiment class is better than the control class. Based on the validation result  obtained  are  valid and  effective learning,  then  the  purpose  of  learning  instrument development is  achieved. Therefore, to improve the  communication  skill  of students in  the linear program materials and other materials with the same characteristics suggested PBL model that has been developed so that the media to improve communication skill math students more varied.Keywords: Project, Communication.